Pengaruh Lingkungan Kerja, Kepemimpinan, dan Motivasi Terhadap Kinerja Karyawan PT. Kereta Api Indonesia (PERSERO) DAOP IV Semarang (Studi Pada PT.Kereta Api Indonesia Wilayah Kota Semarang) - Dwi Rachma Apriani; Wahyu Hidayat (Jurnal Ilmu Administrasi Bisnis, 2016)
The research was distributed by growing companies in Indonesia good manufacturing company or company engaged in the service, one of these transport services. The growing demand for air transportation services in Indonesia. Along with the increased demand, human resources has a large role in determining the success of a service company. Thus required human resources that have a good performance so that it is able to serve the consumer well. The purpose of doing research is to know the influence of work environment, leadership and motivation against the performance of the employees of this company.The population in this study are all employees of the Division of finance, human resources and the public as much as 40 respondents with the sampling technique used is a non probability samples. The analysis of the data used in this study is using SPSS program 23.0, where previously conducted a test of the validity, reliability, correlation coefficient, coefficient of determination, simple and multiple regression analysis, and test of significance (t-test and F-test) in advance. The results of this study indicate that the work environment, leadership, and motivation as well as simultaneous partially affect the performance of the employees.Motivational variables give greater influence on performance of employees compared with environment variables and variable labor leadership. The suggestions can be submitted is for this company pay more attention to the comfort of employees in doing work, such as the layout of the workspace, more fast and right decisions and openness between superiors and subordinates, and rewards in the form of praise for employee achievement.